2020
DOI: 10.1080/17454832.2020.1752756
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of collage art-based and narrative self-expression among home hospice caregivers

Abstract: Aims: This mixed methods quasi-experimental study examined the outcomes of a brief art therapy-based and a narrative interview-based intervention to address the psychosocial needs of home hospice caregivers. Methods: Participants (n = 14) chose to participate either in a narrative interview (n = 7) or artsbased interview (n = 7). Standardised self-report measures of affect, spiritual well-being, perceived stress, and self-efficacy and physiological markers of stress(salivary cortisol) and social/emotional conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…This result is in line with the comprehensive meta-analysis conducted by Khory et al (2013) , who have identified strong evidence to support the efficacy of mindfulness-based therapies in reducing anxiety, depression, and stress among clinical populations with consolidated effect sizes ranging from small to medium in pre-post comparison and waitlist-control studies. The result is also aligned with the burgeoning body of research that has reported creative self-expression through art making and art-based narratives as an important vehicle for burnout reduction and wellness promotion among healthcare workers ( Huet and Holttum, 2016 ; Huet, 2017 ; Tjasink and Soosaipillai, 2019 ; Kaimal et al, 2020 ). Of note, treatment gains in reduced mental exhaustion were not only maintained but also enhanced by a 5-folds increase in effect size at 12-weeks follow-up.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This result is in line with the comprehensive meta-analysis conducted by Khory et al (2013) , who have identified strong evidence to support the efficacy of mindfulness-based therapies in reducing anxiety, depression, and stress among clinical populations with consolidated effect sizes ranging from small to medium in pre-post comparison and waitlist-control studies. The result is also aligned with the burgeoning body of research that has reported creative self-expression through art making and art-based narratives as an important vehicle for burnout reduction and wellness promotion among healthcare workers ( Huet and Holttum, 2016 ; Huet, 2017 ; Tjasink and Soosaipillai, 2019 ; Kaimal et al, 2020 ). Of note, treatment gains in reduced mental exhaustion were not only maintained but also enhanced by a 5-folds increase in effect size at 12-weeks follow-up.…”
Section: Discussionsupporting
confidence: 65%
“…The result is also aligned with the burgeoning body of research that has reported creative self-expression through art making and art-based narratives as an important vehicle for burnout reduction and wellness promotion among healthcare workers (Huet and Holttum, 2016;Huet, 2017;Tjasink and Soosaipillai, 2019;Kaimal et al, 2020). Of note, treatment gains in reduced mental exhaustion were not only maintained but also enhanced by a 5-folds increase in effect size at 12-weeks follow-up.…”
Section: Interpreting the Findingssupporting
confidence: 69%
“…• different crayons and felt pens, in pastel shades and bright colours, selected based on colour psychology [54,55] and to allow free painting from the imagination [69] • play-dough clay, based on research about haptics and using sandboxes to express oneself [69] • a set of 30 postcards/photos (10 per emotion), based on the notion that the process of selecting images is likely to be an expression of self-expression, facilitates spontaneity and represents self-opening [34] and that the so called magazine picture collage technique is beneficial for people without artistic talent [14]. Those images can depict any context, e.g.…”
Section: Materialmentioning
confidence: 99%
“…Collage is a popular practice in which participants select various materials and images, compose them, and attach them to a surface ( Raffaelli and Hartzell, 2016 ; Russo-Zimet, 2016 ; Kaimal et al, 2020 ). Collage-making is an effective way of helping older adults process their memories and life experiences ( Stallings, 2010 ; Keisari et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%